2008
DOI: 10.1111/j.1471-0528.2008.01738.x
|View full text |Cite
|
Sign up to set email alerts
|

Glove perforations during open surgery for gynaecological malignancies

Abstract: Objective To audit glove perforations at laparotomies for gynaecological cancers.Setting Gynaecological oncology unit, cancer centre, London.Design Prospective audit.Sample Twenty-nine laparotomies for gynaecological cancers over 3 months.Methods Gloves used during laparotomies for gynaecological cancer were tested for perforations by the air inflation and water immersion technique. Parameters recorded were: type of procedure, localisation of perforation, type of gloves, seniority of surgeon, operation time an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
25
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 29 publications
2
25
0
4
Order By: Relevance
“…Of those procedures, the variation in perforation rates ranged from 4.0% to 63.0%. As reported by Manjunath et al, 4 gynaecological operations (93.1%) had the highest perforation rate in terms of the number of perforations (at least 1 glove perforation in 1 operation), followed by orthognathic surgery in the present study (91.1%) and open lung surgery (78.0%). 12 The perforation rate in scrub nurses in orthognathic surgery in the present study was 63.4%, nearly the same as that in operators in the gynaecological operation described above (63.0%).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Of those procedures, the variation in perforation rates ranged from 4.0% to 63.0%. As reported by Manjunath et al, 4 gynaecological operations (93.1%) had the highest perforation rate in terms of the number of perforations (at least 1 glove perforation in 1 operation), followed by orthognathic surgery in the present study (91.1%) and open lung surgery (78.0%). 12 The perforation rate in scrub nurses in orthognathic surgery in the present study was 63.4%, nearly the same as that in operators in the gynaecological operation described above (63.0%).…”
Section: Discussionsupporting
confidence: 74%
“…12 The perforation rate in scrub nurses in orthognathic surgery in the present study was 63.4%, nearly the same as that in operators in the gynaecological operation described above (63.0%). 4 This result suggests that the orthognathic surgical team has a higher risk of cross-contamination, particularly the scrub nurse, who manages the surgical instruments even though he or she has no direct contact with patients during the surgery. With regard to other oral and maxillofacial surgeries, the perforation rate in this study was 7.6% in surgeons, which was almost in line with other previous studies (4.0 11 and 6.7% 10 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, several studies have shown that undetected perforations of surgical gloves are common and that the frequency of such defects increases with the duration of glove wear [10][11][12][13]. The risk of glove defects is related to the type of surgery being done, ranging from 7% in urologic surgery to 65% in cardiothoracic surgery [14][15][16][17][18].…”
mentioning
confidence: 97%
“…
Needle stick injuries are a preventable healthcare hazard Sir, I congratulate Manjunath et al 1 for their article that highlights an issue deserving of greater prominence in health care than it currently receives. Glove perforations and associated needle stick injuries are healthcare hazards that place us at risk of catching any of a large number of blood-borne infections, including but not limited to hepatitis B/C and HIV.
…”
mentioning
confidence: 99%